2011
DOI: 10.3415/vcot-10-04-0051
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor concentrations in the synovial fluid from healthy dogs and dogs with secondary osteoarthritis

Abstract: This study demonstrates for the first time the presence of NGF in canine synovial fluid and its increased concentrations in dogs with chronic lameness compared to healthy dogs and dogs with acute lameness. The association between chronic lameness and raised synovial concentrations may suggest an involvement of NGF in OA inflammation and chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…For example, NGF immunoreactivity was shown in dorsal spinal ganglia in experimental radiculopathy 18 . A similar overexpression of neuropeptides including NGF is found in animal models with experimentally induced arthritis 1921 and OA in dogs 22 . These robust NGF-related reactions following pain and inflammation suggest that anti-NGF regimens may result in a reduction of pain perception.…”
Section: Animal Studies – Pain and Effect Of Anti-ngf Regimenssupporting
confidence: 67%
“…For example, NGF immunoreactivity was shown in dorsal spinal ganglia in experimental radiculopathy 18 . A similar overexpression of neuropeptides including NGF is found in animal models with experimentally induced arthritis 1921 and OA in dogs 22 . These robust NGF-related reactions following pain and inflammation suggest that anti-NGF regimens may result in a reduction of pain perception.…”
Section: Animal Studies – Pain and Effect Of Anti-ngf Regimenssupporting
confidence: 67%
“…While local injection of NGF has consistently shown to produce mechanical hyperalgesia in humans 17, 55, 60 and animals 26, 39, 44 , the expression of NGF in the peritoneal fluid of patients with endometriosis seems not to be proportional to pain levels 8 . Such a lack of correlation between pain and local NGF levels has been observed in humans 46 and animals 27 suffering from osteoarthritis, a condition where the pain is sensitive to monoclonal antibodies directed against NGF 14 . This might indicate that NGF acts synergistically with other pro-algesic mediators, its local levels not necessarily being representative of its full involvement in endometriosis pain.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of OA, intra-articular injections of NGF produced prolonged weight-bearing asymmetry. NGF is also upregulated in the synovial fluid of dogs with OA secondary to other conditions [11]. Pecchi et al showed that in a culture of human OA chondrocytes, mechanical stress and exposure to interleukin (IL)-1β increased expression of NGF [12].…”
Section: Pain Mechanisms In Oamentioning
confidence: 99%